A Comparative Study to Assess the Knowledge on Myths and Misconceptions about Mental Illness among Adults (18-35yrs) in Selected Rural and Urban Community of Gurugram with a View to Develop Information Booklet (International Journal of Nursing Education, 2020)
Background: Mental Health is vital for the growth and productivity of every society and for a healthy andhappy life. Mental disorders account for nearly 12% of the global burden of disease. By 2020 they willaccount for nearly 15% of disability-adjusted life-years lost to illness. The burden of mental disorders ismaximal in young adults; the most productive section of the population. However, they can affect anyoneregardless of age, race, religion or income. About one in four adults experiences a diagnosable mentaldisorder in a given year. Mental illness is believed to be associated with myths and misconceptions.Objectives: 1. To assess the level of knowledge on myths and misconceptions about mental illness amongadults in selected rural and urban community of Gurugram. 2. To compare the level of knowledge on mythsand misconceptions about mental illness among adults in selected rural and urban community of Gurugram.3. To find out the association between the level of knowledge on myths and misconceptions about mentalillness among adults with selected demographic variables. 4. To develop and validate an information bookleton myths and misconceptions about mental illness based on the identified needs.Material and Method- A research approach for the study was quantitative approach; and comparativedescriptive research design was selected for the study. The study was conducted at Budhera village andFarukhnagar of Gurugram, Haryana. The population of the study consisted of adults 18-35 years. Nonprobability convenient sampling technique was used to collect the data. The data was collected from 100samples using structured knowledge questionnaire and the collected data was analyzed by using descriptiveand inferential statistics.Results: The study findings revealed that the majority of the adults of urban community i.e. 96% hadgood knowledge followed by 4% average and no one had poor knowledge on myths and misconceptionregarding mental illness. It also shows that the majority of the adults of rural community i.e. 74% hadaverage knowledge followed by only 26% had good knowledge and no one had a poor knowledge on mythsand misconception regarding mental illness.Conclusion: It was concluded that adults of urban community had good knowledge and the adults of ruralcommunity had average knowledge on myths and misconception about mental illness.
Keywords: Mental Illness, Myths and misconception, Knowledge, Adult, Urban and Rural community, Information booklet.